المبادلة التفاعلية في القرآن الكريم -مقاربة تداولية- - بداش حنيفة (University of Eloued جامعة الوادي, 2023)
يروم هذا البحث الوقوف على الخصائص التداولية للحوار، ومنها الولوج إلى أنواعه المختلفة لنسلّط الضّوء على المبادلة على وجه الخصوص، والجانب التّفاعلي لها داخل البنية الحوارية ككل، ودور أنواع المبادلة في التناسل الحجاجي، لنقف بعد هذا المسار التحليلي على أهمية هذا الطرح التداولي والحجاجي لـ "جاك موشلار"(Jacques Mocshler)؛ حينما أحاط الحوار بأشكاله المختلفة بأدوات تحليل خاصّة ومن زاوية مغايرة، وهذا الأخير استقطب أهم عنصر تداولي وهو (التفاعل)، علما أنّه انطلق من الحجاج الخطابي وبرؤية تداولية. مما مكّنه من الظّفر بكل خصوصيات الخطاب وتفاصيله وأشكاله. فباتت المبادلة مسرحا للتّبادل التّواصلي التّفاعلي بين المرسِل والمرسَل إليه. في الخطاب عامّة وفي النّص القرآني على وجه الخصوص؛ إذ تعكس تداولا مرتبطا بسياقات التّخاطب المتنوّعة، وهي سياقات شديدة الخصوصية. فسلّطنا الضّوء هنا على صيغة ووظيفة المبادلة في القرآن الكريم تداولية كانت أم استدلالية. لنثبت في النّهاية أهمّيتها في شكل خطابي معيّن (الحوار)، ودورها في تحقيق الانسجام بين المتخاطبين؛ كونها تستند إلى الخلفيات المشتركة بينهم، وبين الوحدات المشكّلة للنّص. Abstract : This research aims to identify the pragmatic characteristics of the dialogue, then to have access to its different types, and to shed light on the exchange in particular. Also, it aims to shed light on the interactive aspect of the exchange within the dialogue structure as a whole, and on the role of its types in the argumentative intercourse. After this analytical path, the importance of the pragmatic and argumentative proposition of "Jacques Mocshler" is treated; when he surrounded the dialogue in its various forms with special analysis tools and from a different angle. Jacques Mocshler attracted the most important pragmatic element, which is (interaction), knowing that he started from the discourse argumentation and with a pragmatic vision. This enabled him to capture all the peculiarities, details and forms of the discourse. The exchange became a stage for the interactive communicative exchange between the sender and the addressee, in discourse in general and in the Quranic text in particular. It reflects a pragmatic exchange related to the diverse contexts of discourse, which are very specific contexts. This research sheds light here on the formula and function of exchange in the Noble Quran, whether it was pragmatic or deductive. Finally, it proves its importance in a specific form of discourse (the dialogue), and its role in achieving harmony between the interlocutors; it is based on the common backgrounds between them and the text-forming units.
Keywords: المبادلة; التفاعل; الحوار; التداولية; الحجاج